(untitled) (Ukrainian Journal of Ophthalmology, 2025)
This is an initiative study. Cherubism as a form of fibrous dysplasia of jaw bones is a congenital hereditary abnormality of osseous tissue maturation. Although the disease requires mostly maxillofacial surgery and orthodontic care, patients also have to be consulted by an ophthalmologist. The purpose of this study was to share our experience in the diagnostic assessment and treatment of cherubism, a rare form of fibrous dysplasia that is commonly misdiagnosed, which results in inadequate treatment and may lead to serious ocular complications. We present our experience of diagnostic assessment and treatment of four patients with cherubism for one to twenty years. The diagnosis of cherubism became evident after histological study of the material excised during surgery, because postoperative histology showed that changes were not cancerous (adamantinoma), but dysplastic. In addition, new foci developed or old foci recurred some time after surgery. Consequently, true jaw tumors must be correctly differentiated from dental cysts and from dysplastic bone lesions. Patients were followed up once every 6 months. Over the period of follow-up, ocular involvement was observed in the woman who had been diagnosed in childhood with congenital mixed astigmatism. Given our observations, one may make a conclusion that cherubism, a rare form of fibrous dysplasia, is a hereditary or familial disorder, and regresses after completion of puberty and puberty-related changes in hormonal milieu. Timely orthodontic care (and, if required, maxillofacial surgery care) will facilitate preventing the progression of the disease and its ophthalmological consequences. Special attention of ophthalmologists should be paid to cherubism patients with maxillary lesions.